96.8k views
5 votes
What is the recursive rule for the sequence?

What is the recursive rule for the sequence?-example-1
User Almarc
by
6.4k points

1 Answer

5 votes

ANSWER


a_n=a_(n-1) - 13.8 \: where \: \: a_1 = - 7.4

Step-by-step explanation

The given sequence is

-7.4, -21.2,-35,-48.8,-62.6,...

The first term of this sequence is


a_1=-7.4

The constant difference can be calculated using any two consecutive terms:


d = - 35 - - 21.2 = - 13.8

The recursive rule is given by;


a_n=a_(n-1)+d

We plug in the values to get,


a_n=a_(n-1) + - 13.8


a_n=a_(n-1) - 13.8 \: where \: \: a_1 = - 7.4

The correct choice is A.

User Xring
by
6.0k points